Consequential LCA of demountable and reusable internal wall assemblies: a case study in a Belgian context. (August 2019) - Buyle, M; Galle, W; Debacker, W; Audenaert, A
Abstract: The transition from a linear to a circular economy is essential to reduce the environmental burden of our society. A key issue is to prevent a shift of the environmental burdens and take the consequences of a decision into account, for example based on a consequential life cycle assessment (LCA). However, limited practical guidance is available on how to implement consequential LCA in the context of the construction sector. Therefore, the aim of this study is twofold. First, to quantify the potential environmental and burdens of introducing circular design alternatives for internal wall assemblies to the Belgian market. Second, to review the methodological implications on the results of a consequential LCA with a particular focus on consistently identifying marginal suppliers and substitution routes, acknowledging the time dependence and closed-loop nature of the design alternatives. In total seven wall assemblies are assessed over a period of 60 years, with a refurbishment every 15 year. The results show that a low life cycle impact can be achieved for assemblies that are designed to be used again and have a higher initial impact, such as a plywood boarding connected reversibly to a demountable metal frame substructure, as well as for assemblies with no possibilities for direct reuse that have a low initial impact, such as a drywall system with a wooden substructure. Further, regarding the methodological scenarios on marginal supplier identification, the range of possible outcomes is however much larger for the demountable wall assemblies than for the conventional ones.